2003
DOI: 10.1002/humu.10243
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and polymorphisms in the human methyl CpG-binding protein MECP2

Abstract: Rett syndrome (RTT or RS) is a neurodevelopmental disorder and one of the most frequent genetic diseases in girls. Mutations of the MECP2 gene have been found in a variety of different RTT phenotypes. The MECP2 gene (Xq28) has been described in 1992. Up to now, 218 different mutations have been reported in a total group, of more than 2,100 patients. Mutations in the MECP2 gene are responsible for up to 75% of the classical RTT cases. The mutations, are distributed along the whole gene and are comprised of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 82 publications
1
50
1
1
Order By: Relevance
“…Up to 80% of individuals with RTT have mutations 2,3 in exons 3 and 4 of the four-exon gene MECP2 (Fig. 1a) 4 encoding the transcriptional repressor MeCP2.…”
mentioning
confidence: 99%
“…Up to 80% of individuals with RTT have mutations 2,3 in exons 3 and 4 of the four-exon gene MECP2 (Fig. 1a) 4 encoding the transcriptional repressor MeCP2.…”
mentioning
confidence: 99%
“…We were unable to sample and test the parental DNA, but we did not detect this mutation in 100 of the normal controls, as determined with DHPLC. This preferential location may reflect the functional importance of the domains or might be the consequence of a marked sequence-specific hypermutability region (Miltenberger-Miltenyi and Laccone 2003). The study presented herein represents mutation data from a Chinese population consisting of 121 sporadic RTT patients, 107 and 14 of whom presented with classic or atypical RTT, respectively.…”
Section: Cdkl5 Mutation Detection By Dhplc Analysismentioning
confidence: 99%
“…Parental testing showed that the Xp22 duplications were inherited from the mother in four patients (1, 3, 6, and 7) and from the father in one patient (2). Samples of biological parents for patients 4 and 5 were unavailable.…”
Section: Array Cgh Analysesmentioning
confidence: 99%